2021
DOI: 10.1096/fasebj.2021.35.s1.03797
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of student performance following in‐person or virtual gross anatomy labs during COVID‐19

Abstract: The global pandemic of coronavirus disease has significantly impacted medical education, including removing trainees from clinical environments, transitioning didactic sessions to virtual platforms, and necessitating creative solutions to provide interactive learning opportunities in a virtual, socially distant setting. Human gross anatomy education, with its emphasis on hands‐on, team‐based, active learning by body donor dissection, has been particularly impacted by these transitions. Dissection is considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…These results suggest that online NPT of anatomy is comparable to the previous in-person format. Relative equivalence in student assessment performance after a move to online learning in the anatomical sciences has been observed by other authors (Pinder et al, 2008;Inuwa et al, 2012;Beale et al, 2014;Pei and Wu, 2019;Hillmer et al, 2021). The overall student assessment scores in this study further establish that student assessment performance following online anatomy NPT is as effective as in-person NPT.…”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that online NPT of anatomy is comparable to the previous in-person format. Relative equivalence in student assessment performance after a move to online learning in the anatomical sciences has been observed by other authors (Pinder et al, 2008;Inuwa et al, 2012;Beale et al, 2014;Pei and Wu, 2019;Hillmer et al, 2021). The overall student assessment scores in this study further establish that student assessment performance following online anatomy NPT is as effective as in-person NPT.…”
Section: Discussionsupporting
confidence: 82%
“…Although conversational turn-taking was associated with positive measures of social interaction, it is important to note that we did not identify differences in observed performance and subjective experience measures between the conditions for any of the three tasks. These results are similar to those of prior studies that found no differences in perceived effectiveness and performance in association with virtual interaction [4][5][6][7][8][9] . Thus, our findings that video conferencing affects social interaction at the behavioral level, but not subjective or performance level, may help to clarify some of the inconsistent findings in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…Research in this area, however, has produced mixed findings as to whether video conferencing has negative, positive, or no impact on the quality of social interaction. Some studies have found that virtual interactions are no different from in-person interactions in terms of perceived effectiveness and performance in administering neuropsychological assessments 5 , psychotherapy 6 , educational activities 7,8 , facilitating social connectedness 9 , and participating in leisure activities such as yoga 4 . In contrast, other studies found that virtual interaction led to or was associated with a reduction in perceived therapeutic skills 10 and reduced memory function in health care workers 11 , a decline in exam performance 12 , and increased communication and management problems in the workplace 13 .…”
Section: Introductionmentioning
confidence: 99%